Determinants of Health Care Expenditure in Poland in the Years 2014-2023 - Traczyk, Kornelia (Olsztyn Economic Journal, 2025)
This study aimed to assess the development of healthcare expenditure in Poland and identify its determinants. Changes in the structure of this expenditure were analysed, as was its share of Gross Domestic Product (GDP), and the amount of healthcare expenditure per capita in Poland between 2014 and 2023 was calculated and evaluated. During the period under review, healthcare expenditure in Poland was growing, but both its share of GDP and its per capita level were lower than the average in other EU countries The determinants of healthcare expenditure in Poland were identified, dividing them into: legal, macroeconomic, political, unexpected events, demographic, social, environmental, technological, systemic and those resulting from globalisation processes. Determinants were divided into those dependent and independent of the state, pointing to possible ways of dealing with them. The biggest barrier to the growth of healthcare expenditure in Poland is macroeconomic in nature, as it results from the country’s GDP. Other significant problems related to the development of healthcare expenditure result from the ageing of the population and systemic errors. During the analysed period, the Covid-19 pandemic was also a significant factor in the development of healthcare expenditure in Poland.